Do patients in developing world get dignified anesthetic care? - Joshi, Hem Raj (Journal of Society of Anesthesiologists of Nepal, 2017)
This article shares the experiences of two patients undergoing a colonoscopy without any sedation or anaesthesia. The author raises the question whether patients from the developing countries get proper treatment options while undergoing invasive procedures which may require sedation or anaesthesia.